Effect of Job Description and Employee Performance of PDAM Tirta Musi Distribution Palembang - Iin Karlina; Heriyanto Heriyanto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine how the job description on employee performance of PDAM (local water company). This research is a quantitative descriptive study; this study uses a saturated sample where the sampling technique is used when all population members are used as samples. The number of samples in this study was 31 employees of the rambutan service unit in the distribution section of PDAM Tirta Musi Palembang. Data analysis was performed using the technique of Simple Linear Regression Analysis, Correlation Coefficient Analysis, R² Determination Coefficient Analysis, and T-Test (partial). For the study results using SPSS version 25, showing an R-value of 0.485, the job description has a moderate relationship between variables. The results of the coefficient of determination R² of 0.209 means that the job description affects 20.9% of employee performance, and the remaining 79.1% is influenced by other variables outside of this research variable. Furthermore, for the results of the T-test (Partial) in this study, a positive and significant effect on employee performance where HO is rejected and Ha is accepted.